-5x + x + 9 = -4x + 12

Question

Asked 10/3/2012 9:26:08 AM

Updated 6/7/2014 2:18:52 PM

2 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by andrewpallarca [6/7/2014 2:18:52 PM]

s

thederby|Points 1479|

Question

Asked 10/3/2012 9:26:08 AM

Updated 6/7/2014 2:18:52 PM

2 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by andrewpallarca [6/7/2014 2:18:52 PM]

Rating

3

-5x + x + 9 = -4x + 12;

-4x + 9 = -4x + 12;

-4x + 4x = 12 - 9;

0 = 3

For equation -5x + x + 9 = -4x + 12, there is no solution that exists.

-4x + 9 = -4x + 12;

-4x + 4x = 12 - 9;

0 = 3

For equation -5x + x + 9 = -4x + 12, there is no solution that exists.

Added 6/7/2014 2:18:44 PM

This answer has been confirmed as correct and helpful.

32,019,328

questions answered

There are no comments.